Analisis biaya pengeluaran produk impor elektorik dari pelabuhan ke gudang importer dengan analisis rantai pasok dan Model Sistem Dinamis menggunakan Powersim - Nyimas Desy Rizkiyah; Robiyatul Adawiyah (Operations Excellence: Journal of Applied Industrial Engineering, 2020)
The calculation on the expenditure of imported electronic products from the port to the importer's warehouse is very essential in estimating reasonable and competitive prices in the market. For this reason, The Importer “XYZ” processes the expenditure costs incurred in importing activities. In this study, the simulation technique of the Powersim program is used to carry out the calculation of these costs. The results of model simulation in the base year 2020 with a study period of 10 years and 10% increase of importage container will result the cost of IDR 3.115.260.500 in 2020 to become IDR 8,080,183,433 in 2030.